Comprehensive Midwifery Care For Ny’’H’’ With Normal Pregnancy At Bontobangun Health Center,Rilau Ale District,Bulukumba Regency - Asririn, Asririn; Juniarli, Sri Eka; Irmawati, Irmawati (Hayyan Journal, 2025)
Midwives play an important role in efforts to improve maternal and child health, one of which is by implementing comprehensive midwifery care. Midwifery care is carried out to detect early things that may occur during pregnancy, childbirth, newborns, postpartum, neonates and family planning services. The aim is to provide comprehensive care to Mrs "H" aged 25 years from pregnancy, childbirth, postpartum, newborn, and contraceptive services. The method used in providing comprehensive midwifery care is a case study with a Varney management approach with data collection techniques including observation, interviews, physical examination and documentation studies. Results of comprehensive midwifery care for Mrs. , male gender, postpartum progress is normal and the contraception you want to use after the postpartum period is the birth control implant. Conclusion: Comprehensive midwifery care for Mrs "H" was carried out according to standards of care. Carried out according to standards of comprehensive midwifery care that is running normally.